New species of Grubeulepis Pettibone, 1969 (Eulepethidae, Annelida) from northern Brazil - Cutrim, Allana Stéphanie Tavares; Praseres, Emanuelle Fernandes; Conceição, Jhully Mickaelly Vermont Silva; de Almeida, Zafira Da Silva; Júnior, Miodeli Nogueira; de Oliveira, Verônica Maria (Zootaxa, 2018)
Eulepethidae is one of the least diverse families of scale polychaetes, with only 23 species described thus far. In this study we describe an additional species of Grubeulepis from unconsolidated substrata from Maranhão, tropical Brazil (ca. 2°S). Grubeulepis serrata sp. nov. differs from other species of the family due to the presence of one pair of eyes, 14 pairs of branchiae, posterior lamellae beginning in the 27th segment, with hooked upper notochaetae and serrated outer edge acicular neurochaeta in the 3rd segment. The diagnosis of the genus formerly included species with 10–13 pairs of branchiae, and thus is modified to accommodate the 14 pairs of branchiae from the new species described here. Grubeulepis serrata sp. nov. shares with Grubeulepis mexicana (Berkeley & Berkeley 1939) the number of lateral processes of the 12th elytra, the segment of the foliaceous lamellae and the presence of acicular neurochaeta in the 3rd segment, but they differ in the number of branchiae pairs, eyes and the notochaetae shape. Grubeulepis serrata sp. nov. shares with Grubeulepis geayi (Fauvel 1918) the spiny notochaetae with spoon-shaped distal end, but differ in the hooked upper notochaetae, amount of lateral processes, and elytra articulation.